THE IMPLEMENTATION OF IJARAH MUNTAHIYA BITTAMLIK AND MUDHARABAH PRODUCTS IN THE SHARIA ECONOMIC LAW PERSPECTIVE - Mu’minah, Mimin (Journal of Economicate Studies, 2018)
This article is motivated by the rapid development of the Islamic banking world, especially in Indonesia where the majority of the population is Muslims. When other countries have given birth to Islamic-based banks, as well as Indonesia, in 1992 was the establishment of Bank Muamalat Indonesia. Islamic banks use applications that are different from conventional banks, where the term on conventional banks is interest, whereas in Islamic banks use the profit sharing application. One application of Islamic banks that is very helpful to customers is the Mudharabah and Ijarah Muntahiya Bittamlik (IMBT) application. Although these two applications exist in Islamic banks or Islamic-based banks, it is possible that the two applications are not in accordance with Islamic economic law. Therefore, this paper tries to analyze the mudharabah and IMBT applications in the perspective of sharia economic law.